Theranostic Approach in Breast Cancer: A Treasured Tailor for Future Oncology. (August 2021) - Jokar, Narges; Velikyan, Irina; Ahmadzadehfar, Hojjat; Rekabpour, Seyed Javad; Jafari, Esmail; Ting, Hong Hoi; Biersack, Hans-Jürgen; Assadi, Majid
Abstract : Abstract: Breast cancer is the most frequent invasive malignancy and the second major cause of cancer death in female subjects mostly due to the considerable diagnostic delay and failure of therapeutic strategies. Thus, early diagnosis and possibility to monitor response to the treatment are of utmost importance. Identification of valid biomarkers, in particular new molecular therapeutic targets, that would allow screening, early patient identification, prediction of disease aggressiveness, and monitoring response to the therapeutic regimen has been in the focus of breast cancer research during recent decades. One of the intensively developing fields is nuclear medicine combining molecular diagnostic imaging and subsequent (radio)therapy in the light of theranostics. This review aimed to survey the current status of preclinical and clinical research using theranostic approach in breast cancer patients with potential to translate into conventional treatment strategies alone or in combination with other common treatments, especially in aggressive and resistant types of breast cancer. In addition, we present 5 patients with breast cancer who were refractory or relapsed after conventional therapy while presumably responded to the molecular radiotherapy with 177 Lu-trastuzumab (Herceptin), 177 Lu-DOTATATE, and 177 Lu-FAPI-46.